Cementitious material for improving performance of interface area between new and old concrete of laminated slab and construction method

CN116693269BActive Publication Date: 2026-10-09JIAHUA SPECIAL CEMENT +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310591144.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-24
Publication Date
2026-10-09
Estimated Expiration
2043-05-24

AI Technical Summary

Technical Problem

但该界面剂无法消除界面区附近密实度较低的氢氧化钙,且界面剂施工需要两次涂刷才能完成

Benefits of technology

[0068] (1) Compared with conventional sulfoaluminate cement and aluminate cement, the AFt, AFm, and C4AH produced by the reaction of non-crystalline calcium aluminate, gypsum, and ultrafine silicate cement (ultrafine PⅠ52.5 cement) are superior. 13 C3AH6 is finer and easier to fill pores in old concrete surfaces; in addition, C4AH has finer crystals. 13 With high surface energy, it readily reacts with Ca(OH)2 generated from new concrete to form ettringite, greatly improving the performance of the interface zone between new and old concrete in composite slabs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116693269B_ABST
    Figure CN116693269B_ABST
Patent Text Reader

Abstract

The application discloses cementitious material for improving performance of new and old concrete interface area of laminated slab and a construction method. The cementitious material comprises the following raw materials in parts by weight: non-crystalline calcium aluminate cementitious material: 58-69.5 parts; permeable active silicon solution: 30-40 parts; and wollastonite: 0.5-2 parts. The application can effectively improve the bonding capacity of the new and old concrete interface of the laminated slab and improve the durability of the laminated slab, and the cementitious material is simple to prepare, has uniform component distribution and is convenient to construct.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of concrete materials technology, specifically relating to cementitious materials and construction methods for improving the performance of the interface zone between new and old concrete in composite slabs. Background Technology

[0002] Precast concrete structures (referred to as precast structures) are structural systems formed by assembling / connecting precast components (such as precast beams, slabs, and columns) as the main load-bearing members. Floor slabs are crucial load-bearing components in precast structures, responsible for bearing and transferring loads. They are generally classified into three types: precast floor slabs (assembled from precast slabs), cast-in-place slabs, and precast monolithic floor slabs (i.e., composite floor slabs). Composite slabs, composed of a precast base slab and a post-cast layer, combine the advantages of both precast and cast-in-place floor slabs and have gained widespread application in recent years. However, due to the uneven microstructure of the interface between the precast base slab and the post-cast layer, this interface exhibits high porosity, low hardness, and contains a large number of low-density calcium hydroxide crystals. Numerous studies have found that the bond strength between new and old concrete is low, resulting in poor durability, and these new concrete layers are often the first to fail under long-term loads. Therefore, in composite slab structures, the interface between the precast and post-cast parts (i.e., the interface area) is the weakest area in the overall structure, with poor mechanical and durability properties.

[0003] To improve the performance of the interface between new and old concrete (interface zone), Chinese invention patent application number 202211316639.1, entitled "An interface agent for enhancing the bonding performance of new and old concrete and its construction method," discloses an interface agent for enhancing the bonding performance between new and old concrete. The interface agent's raw materials include cement, limestone powder, water, polymer emulsion, quartz sand, high-efficiency water-reducing agent, and defoamer. It can effectively improve the bonding performance between new and old concrete, and enhance the mechanical properties, fracture properties, and durability properties of concrete structures such as impermeability and erosion resistance. However, this interface agent cannot eliminate the low-density calcium hydroxide near the interface zone, and the application of the interface agent requires two coats to complete. Chinese invention patent application number 202011246455.3, entitled "An Interface Agent for Wet Joint Concrete in Prefabricated Buildings and its Preparation Method," provides an interface agent that can recycle waste liquid from the wet-process phosphoric acid production process, reducing environmental pollution. While improving the bond strength at wet joints, it significantly enhances the interfacial impermeability, preventing problems such as water seepage and efflorescence at the joints. However, the compacting agent used in this invention involves a complex process. Furthermore, numerous studies have indicated that adding silica fume to the interface agent allows it to react with the hydration product Ca(OH)2 in the interfacial zone to form CSH gel, generating chemical forces that can improve interfacial strength and better integrate the new and old concrete interfaces. However, nano-sized silica fume materials, due to their nanoscale particle size, tend to agglomerate due to quantum size effects, small size effects, and surface effects. Therefore, eliminating the agglomeration effect of silica fume particles and ensuring uniform dispersion in interface agents is a hot research topic in the industry.

[0004] Therefore, there is a need to provide cementitious materials and construction methods that can improve the performance of the interface between new and old concrete in composite slabs. These materials can not only effectively improve the bonding ability between the new and old concrete in composite slabs and enhance the durability of the composite slabs, but also be simple to prepare, have uniform component distribution, and be easy to construct. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a cementitious material and construction method for improving the performance of the interface zone between new and old concrete in composite slabs, so as to at least solve some of the above-mentioned technical problems.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] Cementitious materials for improving the properties of the interface zone between new and old concrete in composite slabs, comprising the following raw materials in parts by weight:

[0008] Non-crystalline calcium aluminate cementitious material: 58–69.5 parts;

[0009] Permeation activated silica solution: 30-40 parts;

[0010] Wollastonite: 0.5 to 2 parts.

[0011] In some embodiments of the present invention, the gelling material comprises the following raw materials in parts by weight:

[0012] Non-crystalline calcium aluminate cementitious material: 60-66 parts;

[0013] Permeation active silica solution: 35-38 parts;

[0014] Wollastonite: 1-2 parts.

[0015] Furthermore, the amorphous calcium aluminate cementitious material comprises the following components by weight:

[0016] Non-crystalline calcium aluminate: 600-800 parts;

[0017] Ultrafine PⅠ52.5 cement: 97-199 parts;

[0018] Gypsum: 98.5–199.5 parts;

[0019] Borax: 0.5–1.5 parts;

[0020] Melamine water-reducing agent: 1-3 parts;

[0021] The specific surface area of ​​the ultrafine PⅠ52.5 cement is greater than 500 m². 2 / kg.

[0022] In some embodiments of the present invention, the amorphous calcium aluminate cementitious material comprises the following components by weight:

[0023] Non-crystalline calcium aluminate: 650-750 parts;

[0024] Ultrafine PⅠ52.5 cement: 120-180 parts;

[0025] Gypsum: 120-180 parts;

[0026] Borax: 1-1.5 parts;

[0027] Melamine water-reducing agent: 1-2 parts;

[0028] The specific surface area of ​​the ultrafine PⅠ52.5 cement is greater than 500 m². 2 / kg.

[0029] Furthermore, the permeation activated silica solution comprises the following components by weight percentage:

[0030] Alkaline silica sol: 1-2 wt.%;

[0031] Nanoparticle-grade silica fume: 5–10 wt.%;

[0032] Alkali metal carbonates: 1 wt.%;

[0033] Water: 87–93 wt.%;

[0034] The alkaline silica sol has a SiO2 solid content of 20–40 wt.%.

[0035] The wollastonite is fibrous with an aspect ratio of 10 to 15.

[0036] The alkali metal carbonates are strong base weak acid salts such as Na2CO3, Li2CO3, and K2CO3.

[0037] Furthermore, the initial setting time of the cementitious material is 30-45 min, and the final setting time is 55-65 min.

[0038] This invention also provides a construction method for cementitious materials that improve the performance of the interface zone between new and old concrete in composite slabs, characterized by comprising the following steps:

[0039] Step 1: Weigh each ingredient according to the specified proportions;

[0040] Step 2: Mix the weighed amorphous calcium aluminate, ultrafine PⅠ52.5 cement, gypsum, borax and melamine water-reducing agent evenly to form amorphous calcium aluminate cementitious material;

[0041] Step 3: Prepare a permeation-activated silica solution;

[0042] Step 4: Pour the mixed amorphous calcium aluminate cementitious material into the permeating activated silica solution and stir to obtain a slurry.

[0043] Step 5: Pour wollastonite into the slurry and mechanically stir to obtain the cementitious material.

[0044] Step 6: Lower the surface temperature of the concrete slab that has just come out of the curing tank, and then apply the cementitious material to the surface of the hardened concrete (old concrete).

[0045] Preferably, in step 4, the stirring time is 2 minutes;

[0046] Preferably, in step 5, the stirring time is 1 minute;

[0047] Preferably, in step 5, when the surface temperature of the concrete slab drops below 40°C, the cementitious material is applied to the surface of the hardened concrete (old concrete).

[0048] Further, step 3 includes:

[0049] Step 31: Weigh out the alkaline silica sol, nano-sized silica fume, alkali metal carbonate, and water by weight percentage;

[0050] Step 32: Dissolve the alkali metal carbonate completely in water;

[0051] Step 33: Pour the alkaline silica sol into the solution prepared in step 32, and then stir.

[0052] Step 34: Pour the nano-sized silica fume and the solution obtained in step 33 into an ultrafine ball mill and grind them together to obtain a penetrating active silica solution.

[0053] Preferably, in step 33, the stirring time is 0.3 to 0.8 hours, more preferably 0.5 hours;

[0054] Preferably, in step 34, the grinding time is 0.8 to 1.5 hours, more preferably 1 hour.

[0055] Furthermore, in step 4, the consistency of the slurry is 180±10mm.

[0056] Furthermore, in step 6, the coating thickness of the cementitious material is 2-3 mm.

[0057] The mechanism of action of cementitious materials that improve the properties of the interface zone between new and old concrete in composite slabs is as follows:

[0058] (1) After the cementitious material is applied to the surface of the old concrete of the composite slab, the Ca(OH)2 produced by the hydration of ultrafine silicate cement (ultrafine PⅠ52.5 cement) reacts chemically with non-crystalline calcium aluminate and gypsum to generate needle-like AFt (ettringite), AFm (monosulfur type hydrated calcium sulfoaluminate), and cubic C4AH 13 These products, along with flake-like C3AH6, radiate into the capillary pores of the old concrete surface, optimizing the surface pore structure and increasing the micro-roughness, thereby enhancing the mechanical adhesion between the old concrete and the coating layer. When new concrete is poured into the composite slab, the gypsum and Ca(OH)2 in the fresh concrete mix react with C4AH... 13 The reaction generates needle-like AFt, reducing the directional distribution of Ca(OH)2 crystals and increasing the mechanical interlocking force between the new concrete and the coating layer. In summary, the coating layer acts as a medium, increasing the mechanical interlocking force between the new and old concrete in the composite slab, thus improving the bond strength between them.

[0059] (2) Silica sol is a colloidal solution formed by the uniform dispersion of amorphous SiO2 particles in water. The internal structure of silica sol particles consists of silicon-oxygen-silicon bonds (—Si—O—Si—), and the surface layer is covered by silanol groups—SiOH and —Si(OH)2. The silanol groups have good activity and can undergo condensation reactions, leading to self-polymerization between silica sol particles to form silica gel. To avoid self-polymerization of silica sol, this invention dissolves silica sol in an alkaline solution (pH greater than 11) to form alkaline silica sol. - This causes partial dissociation of the silanol groups on the sol surface, resulting in the formation of silicate anions (Si-O).- The increased quantity of silica sols leads to a higher zeta potential in the diffused double layer of the particles, which is unfavorable for the condensation reaction between SiO2 particles and improves the stability of the silica sol in solution. Furthermore, this invention uses borax as a retarder for amorphous calcium aluminate cementitious materials. Borax hydration is alkaline, which does not affect the uniform distribution of the sol in the permeating active silica solution.

[0060] (3) The mineral composition of silica fume is nano-sized amorphous SiO2. Silica fume and silica sol alkaline solution are similarly miscible. When silica fume is dissolved in silica sol solution, the surface of silica fume particles is rich in silicate anions, and the electrostatic repulsion between particles increases, making it difficult to agglomerate. In addition, the particle size of silica fume particles is further reduced by grinding with a ball mill.

[0061] (4) The present invention also improves the interfacial transition zone by permeating an active silicon solution, the principle of which is:

[0062] Old concrete contains numerous capillary channels. The additional stress generated by these capillary channels pulls water onto the concrete surface, meaning that water on the surface is naturally absorbed by the capillary channels. The penetration depth can be expressed by the formula: H = 2γ sl cosθ / rρg is obtained, where γ sl Let ρ be the surface tension of the aqueous solution and the concrete, θ be the contact angle between the aqueous solution and the concrete (θ is less than 90°), r be the capillary radius, ρ be the density of the aqueous solution, and g be the acceleration due to gravity. From the above equation, it can be seen that the penetration depth is determined by the density of the aqueous solution, the capillary radius, and the surface tension.

[0063] First, this invention utilizes the principle of "like dissolves like" and mechanical grinding to prepare a penetrating activated silica solution. In this solution, amorphous SiO2, using water as a carrier, penetrates into or around the old concrete, reacting with the cement hydration product Ca(OH)2 to form a water-insoluble CSH gel. This gel fills and seals the fine cracks, capillaries, pores, and voids on the surface of the old concrete. Once the coating dries, the amorphous SiO2 ceases to penetrate. However, when new concrete is poured, under the influence of concentration difference and surface tension, the amorphous SiO2 will penetrate into or around the new concrete using water as a carrier, improving the density of the new concrete and increasing the cohesion between the old and new concrete.

[0064] Furthermore, the hydration product of amorphous calcium aluminate, Al(OH)3 (aluminum gel, AH3), forms [Al(OH)4] under alkaline conditions. - That is, tetrahydroxyaluminate, [Al(OH)4] - The group is readily soluble in water and can penetrate into the capillary channels of concrete along with the water, reacting with the Ca in the capillary channels. 2+ Alternatively, it reacts with Ca(OH)2 to form calcium aluminate crystals, which intertwine with CSH gel and fill the pores.

[0065] Finally, alkali metal carbonates are not only used as stabilizers for silica sols, but are also readily soluble in water. After the cementitious materials are applied, they can react with Ca(OH)2 in the concrete to generate CaCO3 precipitate, thus improving the interfacial properties between new and old concrete.

[0066] (5) Ca slowly dissolved from wollastonite 2+ The amorphous SiO2 in the permeating active silica solution reacts to form CSH gel, which strengthens the adhesion between wollastonite fibers and the matrix.

[0067] Compared with the prior art, the present invention has the following beneficial effects:

[0068] (1) Compared with conventional sulfoaluminate cement and aluminate cement, the AFt, AFm, and C4AH produced by the reaction of non-crystalline calcium aluminate, gypsum, and ultrafine silicate cement (ultrafine PⅠ52.5 cement) are superior. 13 C3AH6 is finer and easier to fill pores in old concrete surfaces; in addition, C4AH has finer crystals. 13 With high surface energy, it readily reacts with Ca(OH)2 generated from new concrete to form ettringite, greatly improving the performance of the interface zone between new and old concrete in composite slabs.

[0069] (2) Alkaline silica sol is used to dissolve nano-sized silica fume, so that it is evenly and stably distributed in the alkaline solution; mechanical grinding is used to further reduce the particle size of amorphous SiO2 particles and increase the reactivity of amorphous SiO2 with Ca(OH)2.

[0070] (3) Amorphous SiO2 in the penetrating activated silica solution permeates into or around the old concrete using water as a carrier. It reacts with the cement hydration product Ca(OH)2 to form water-insoluble CSH gel, filling and sealing the fine cracks, capillaries, pores, and voids on the surface of the old concrete, increasing the cohesion between the old and new concrete. Hydration product [Al(OH)4] - The group is readily soluble in water and can penetrate into the capillary channels of concrete along with the water, reacting with the Ca in the capillary channels. 2+ Alternatively, it can react with Ca(OH)₂ to form calcium aluminate crystals, which interweave with CSH gel and fill the pores. Alkali metal carbonates are readily soluble in water and, after the cementitious material is applied, can react with Ca(OH)₂ in the concrete through osmosis to form CaCO₃ precipitate, improving the interfacial properties between new and old concrete.

[0071] (4) In traditional research, wollastonite is generally used as a natural fiber in cement concrete products to increase the material's impact resistance, flexural strength, and durability. However, wollastonite has poor adhesion to the matrix and cannot fully exert its toughening and strengthening effects. In this invention, the slowly dissolved Ca from wollastonite is utilized... 2+The amorphous SiO2 in the permeating active silica solution reacts to form CSH gel, which strengthens the adhesion between wollastonite fibers and the matrix. Attached Figure Description

[0072] Figure 1(a) shows the microstructure of the interface between new and old concrete in the composite slab using the cementitious material of the present invention after 28 days.

[0073] Figure 1(b) shows the microstructure of the interface between new and old concrete in a composite slab without the cementitious material of the present invention, 28 days later.

[0074] Figure 2 The image shows the XRD pattern of amorphous calcium aluminate. Detailed Implementation

[0075] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0076] Figure 1(b) shows the microstructure of the interface between new and old concrete in the composite slab without the cementitious material of this invention, after 28 days. The interface between the new and old concrete in the composite slab contains oriented Ca(OH)₂ crystals. Figure 1(a) shows the microstructure of the interface between new and old concrete in the composite slab using the cementitious material of this invention, after 28 days. The products at the interface between the new and old concrete in the composite slab are needle-like AFt and flocculent CSH gel, with the products overlapping each other. Additionally, unhydrated nano-sized SiO₂ particles are present.

[0077] Figure 2 The XRD pattern of amorphous calcium aluminate shows a distinct diffuse peak at a 2θ angle of 25–40°, with an intensity of only 500 cps, indicating that the material is amorphous. Amorphous calcium aluminate possesses higher metastable chemical energy and a faster hydration rate.

[0078] Example 1

[0079] As a preferred embodiment of the present invention, the cementitious material disclosed in this embodiment for improving the performance of the interface zone between new and old concrete in composite slabs includes:

[0080] Non-crystalline calcium aluminate cementitious material: 69.5 parts;

[0081] Permeation activated silica solution: 30 parts;

[0082] Wollastonite: 0.5 parts.

[0083] The non-crystalline calcium aluminate cementitious material includes:

[0084] Non-crystalline calcium aluminate: 600 parts;

[0085] Ultrafine PⅠ52.5 cement: 199 parts;

[0086] Plaster: 199.5 parts;

[0087] Borax: 0.5 parts;

[0088] Melamine water-reducing agent (powder): 1 part;

[0089] The specific surface area of ​​ultrafine PⅠ52.5 cement is 600m². 2 / kg.

[0090] The composition of the permeation active silica solution is as follows:

[0091] Alkaline silica sol: 2 wt.%;

[0092] Nanoparticle-grade silica fume: 10 wt.%;

[0093] Na2CO3: 1 wt.%;

[0094] Water: 87 wt.%;

[0095] The SiO2 solid content of the alkaline silica sol is 20 wt.%.

[0096] Wollastonite is fibrous with an aspect ratio of 10–15.

[0097] Example 2

[0098] As a preferred embodiment of the present invention, the cementitious material disclosed in this embodiment for improving the performance of the interface zone between new and old concrete in composite slabs includes:

[0099] Non-crystalline calcium aluminate cementitious material: 58 parts;

[0100] Permeation activated silica solution: 40 parts;

[0101] Wollastonite: 2 parts.

[0102] The non-crystalline calcium aluminate cementitious material includes:

[0103] Non-crystalline calcium aluminate: 800 parts;

[0104] Ultrafine PⅠ52.5 cement: 97 parts;

[0105] Gypsum: 98.5 parts;

[0106] Borax: 1.5 parts;

[0107] Melamine water-reducing agent (powder): 3 parts;

[0108] The specific surface area of ​​ultrafine PⅠ52.5 cement is 800m².2 / kg.

[0109] The composition of the permeation active silica solution is as follows:

[0110] Alkaline silica sol: 1 wt.%;

[0111] Nanoparticle-grade silica fume: 5 wt.%;

[0112] Li2CO3: 1 wt.%;

[0113] Water 93 wt.%;

[0114] The SiO2 solid content of the alkaline silica sol is 40 wt.%.

[0115] Wollastonite is fibrous with an aspect ratio of 10–15.

[0116] Example 3

[0117] As a preferred embodiment of the present invention, the cementitious material disclosed in this embodiment for improving the performance of the interface zone between new and old concrete in composite slabs includes:

[0118] Non-crystalline calcium aluminate cementitious material: 64 parts;

[0119] Permeation activated silica solution: 35 parts;

[0120] Wollastonite: 1 part.

[0121] The non-crystalline calcium aluminate cementitious material includes:

[0122] Non-crystalline calcium aluminate: 700 parts;

[0123] Ultrafine PⅠ52.5 cement: 148 parts;

[0124] Plaster: 149 parts;

[0125] Borax: 1 part;

[0126] Melamine water-reducing agent (powder): 2 parts;

[0127] The specific surface area of ​​ultrafine PⅠ52.5 cement is 700m². 2 / kg.

[0128] The composition of the permeation active silica solution is as follows:

[0129] Alkaline silica sol: 1.5 wt.%;

[0130] Nanoparticle-grade silica fume: 7.5 wt.%;

[0131] K2CO3: 1 wt.%;

[0132] Water: 90 wt.%;

[0133] The SiO2 solid content of the alkaline silica sol is 30 wt.%.

[0134] Wollastonite is fibrous with an aspect ratio of 10–15.

[0135] Examples 1-3 were all prepared and applied using the following methods:

[0136] Step 1: Weigh each ingredient according to the specified proportions;

[0137] Step 2: Mix the weighed amorphous calcium aluminate, ultrafine PⅠ52.5 cement, gypsum, borax and melamine water-reducing agent evenly to form amorphous calcium aluminate cementitious material;

[0138] Step 3: Prepare a permeation-activated silica solution;

[0139] Step 4: Pour the mixed amorphous calcium aluminate cementitious material into the permeable activated silica solution and mechanically stir for 2 minutes to obtain a slurry with a consistency of 180±10 mm.

[0140] Step 5: Pour wollastonite into the slurry and mechanically stir for 1 minute to obtain the cementitious materials of each embodiment.

[0141] Step 6: Test the surface temperature of the concrete slab immediately after it leaves the curing tank. Only when the surface temperature of the concrete slab drops below 40°C can the cementitious material prepared in each embodiment be applied to the surface of the hardened concrete (old concrete) with a coating thickness of 2-3 mm.

[0142] Step 3, preparing the permeation-activated silica solution, includes the following steps:

[0143] Step 31: Weigh out the alkaline silica sol, nano-sized silica fume, alkaline carbonate, and water by weight percentage;

[0144] Step 32: Dissolve the alkaline carbonate completely in water;

[0145] Step 33: Pour the alkaline silica sol into the alkaline solution prepared in step 32, and turn on the magnetic stirrer to stir for 0.5 hours.

[0146] Step 34: Pour the nano-sized silica fume and the solution obtained in step 33 into an ultrafine ball mill and grind for 1 hour to obtain the permeable active silica solution of each embodiment.

[0147] Comparative Example 1

[0148] Compared with Example 1, this comparative example uses sulfoaluminate cement instead of non-crystalline calcium aluminate cementitious material, while all other conditions are the same.

[0149] Comparative Example 2

[0150] Compared with Example 1, this comparative example uses aluminate cement instead of non-crystalline calcium aluminate cementitious material, while all other conditions are the same.

[0151] The test results of the cementitious materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2 to improve the performance of the interface zone between new and old concrete in composite slabs are shown in Table 1.

[0152] Table 1

[0153]

[0154]

[0155] As shown in Table 1, the cementitious materials provided in Examples 1 to 3 of this invention have a 3-day compressive strength of over 38 MPa and a final setting time of approximately 60 minutes, indicating that the cementitious materials hydrate and harden rapidly, without affecting the construction of the composite slab. Furthermore, the 28-day flexural strength of the cementitious materials exceeds 12 MPa, indicating good toughness, which is beneficial for improving the bonding performance between new and old concrete in the composite slab. Comparative Example 1 uses sulfoaluminate cement instead of amorphous calcium aluminate; due to the large amount of C2S in sulfoaluminate cement, its 3-day strength is relatively low. Comparative Example 2 uses aluminate cement instead of amorphous calcium aluminate; the hydration product of aluminate cement, CAH... 10 The product is easily converted to C3AH6, which reduces the molar volume, increases the matrix porosity, and decreases the 28-day strength.

[0156] After the composite slab was coated with the cementitious materials prepared in Examples 1-3 and Comparative Examples 1-2, the bond performance (bond splitting tensile strength) of the interface between the new and old concrete is shown in Table 2. The splitting tensile test method was performed in accordance with GB / T 50081—2016 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete".

[0157] Comparative molding method: A 150mm cube specimen was cut with a cutting machine, the cut surface was roughened, and after being fully moistened, the specimen was placed in a mold, and new concrete was poured. After 1 day, it was demolded and placed in a standard environment for curing for 28 days. The splitting tensile strength of the interface between the new and old concrete was measured.

[0158] Experimental molding method: A 150mm cube specimen was cut open with a cutting machine, the cut surface was roughened, and after being fully moistened, the cementitious material prepared in Examples 1 to 3 and Comparative Examples 1 to 2 was applied to the cut surface with a thickness of 2 to 3mm. After the cementitious material was fully set, the old concrete was placed in the mold, and new concrete was poured. After 1 day, the specimen was demolded and cured in a standard environment for 28 days. The splitting tensile strength of the interface between the new and old concrete was measured.

[0159] Both the control group and the experimental group used C40 mix proportions for both new and old concrete.

[0160] Table 2

[0161]

[0162]

[0163] As shown in Table 2, the splitting tensile strength at the interface between new and old concrete in the control group was 2.53 MPa, while the splitting tensile strength at the interface between new and old concrete in Examples 1-3 was higher than that in the control group. Specifically, the splitting tensile strength of Example 2 was 4.03 MPa, 1.5 MPa higher than that in the control group. The splitting tensile strength of Comparative Example 1 was 2.91 MPa, only 0.38 MPa higher than that in the control group, while the splitting tensile strength of Comparative Example 2 was slightly higher than that in the control group by 0.04 MPa. The results indicate that the cementitious material prepared in this invention significantly improves the bonding performance between new and old concrete in the composite slab.

[0164] Finally, it should be noted that the above embodiments are merely preferred embodiments of the present invention used to illustrate the technical solutions of the present invention, and are not intended to limit the invention, nor are they intended to limit the patent scope of the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention. That is to say, any changes or refinements made to the main design concept and spirit of the present invention that are not of substantial significance, but whose technical problems are still consistent with the present invention, should be included within the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention to other related technical fields are similarly included within the patent protection scope of the present invention.

Claims

1. A cementitious material for improving the performance of the interface zone between new and old concrete in composite slabs, characterized in that, Including the following raw materials in parts by weight: Non-crystalline calcium aluminate cementitious material: 58~69.5 parts; Permeation activated silica solution: 30-40 parts; Wollastonite: 0.5~2 parts; The non-crystalline calcium aluminate cementitious material is composed of the following components by weight: Non-crystalline calcium aluminate: 600-800 parts; Ultrafine P·I52.5 cement: 97~199 parts; Gypsum: 98.5~199.5 parts; Borax: 0.5~1.5 parts; Melamine water-reducing agent: 1-3 parts; The permeation activated silica solution is composed of the following components by weight percentage: Alkaline silica sol: 1~2 wt.%; Nanoparticle-grade silica fume: 5~10 wt.%; Alkali metal carbonates: 1 wt.% Water: 87~93 wt.%.

2. The cementitious material for improving the performance of the interface zone between new and old concrete in composite slabs according to claim 1, characterized in that, Including the following raw materials in parts by weight: Non-crystalline calcium aluminate cementitious material: 60~66 parts; Permeation activated silica solution: 35-38 parts; Wollastonite: 1-2 parts; The non-crystalline calcium aluminate cementitious material is composed of the following components by weight: Non-crystalline calcium aluminate: 600-800 parts; Ultrafine P·I52.5 cement: 97~199 parts; Gypsum: 98.5~199.5 parts; Borax: 0.5~1.5 parts; Melamine water-reducing agent: 1-3 parts; The permeation activated silica solution is composed of the following components by weight percentage: Alkaline silica sol: 1~2 wt.%; Nanoparticle-grade silica fume: 5~10 wt.%; Alkali metal carbonates: 1 wt.% Water: 87~93 wt.%.

3. The cementitious material for improving the performance of the interface zone between new and old concrete in composite slabs according to claim 1 or 2, characterized in that, The specific surface area of ​​the ultrafine P·I52.5 cement is greater than 500 m². 2 / kg.

4. The cementitious material for improving the performance of the interface zone between new and old concrete in composite slabs according to claim 3, characterized in that, The non-crystalline calcium aluminate cementitious material is composed of the following components by weight: Non-crystalline calcium aluminate: 650~750 parts; Ultrafine P·I52.5 cement: 120~180 parts; Plaster: 120-180 parts; Borax: 1~1.5 parts; Melamine water-reducing agent: 1-2 parts; The specific surface area of ​​the ultrafine P·I52.5 cement is greater than 500 m². 2 / kg.

5. The cementitious material for improving the performance of the interface zone between new and old concrete in composite slabs according to claim 1 or 2, characterized in that, The alkaline silica sol has a SiO2 solid content of 20~40 wt.%; The wollastonite is fibrous with an aspect ratio of 10 to 15.

6. The cementitious material for improving the performance of the interface zone between new and old concrete in composite slabs according to claim 1 or 2, characterized in that, The initial setting time of the cementitious material is 30-45 min, and the final setting time is 55-65 min.

7. A construction method for a cementitious material for improving the performance of the interface zone between new and old concrete in composite slabs as described in any one of claims 1-6, characterized in that, Includes the following steps: Step 1: Weigh each ingredient according to the specified proportions; Step 2: Mix the weighed amorphous calcium aluminate, ultrafine P·I52.5 cement, gypsum, borax and melamine water-reducing agent evenly to form amorphous calcium aluminate cementitious material. Step 3: Prepare a permeation-activated silica solution; Step 4: Pour the mixed amorphous calcium aluminate cementitious material into the permeating activated silica solution and stir to obtain a slurry; Step 5: Pour wollastonite into the slurry and mechanically stir to obtain the cementitious material; Step 6: Reduce the surface temperature of the concrete slab that has just left the curing tank, and then apply the cementitious material to the hardened concrete surface.

8. The construction method of the cementitious material for improving the performance of the interface zone between new and old concrete in composite slabs as described in claim 7, characterized in that, In step 4, the stirring time is 2 minutes; in step 5, the stirring time is 1 minute.

9. The construction method of the cementitious material for improving the performance of the interface zone between new and old concrete in composite slabs as described in claim 7, characterized in that, In step 6, when the surface temperature of the concrete slab drops below 40°C, the cementitious material is applied to the hardened concrete surface.

10. The construction method of the cementitious material for improving the performance of the interface zone between new and old concrete in composite slabs according to claim 7, characterized in that, Step 3 includes: Step 31: Weigh out the alkaline silica sol, nano-sized silica fume, alkali metal carbonate, and water by weight percentage; Step 32: Dissolve the alkali metal carbonate completely in water; Step 33: Pour the alkaline silica sol into the solution prepared in step 32, and then stir. Step 34: Pour the nano-sized silica fume and the solution obtained in step 33 into an ultrafine ball mill for grinding to obtain a permeable active silica solution.

11. The construction method of the cementitious material for improving the performance of the interface zone between new and old concrete in composite slabs according to claim 10, characterized in that, In step 33, the stirring time is 0.3~0.8h; in step 34, the grinding time is 0.8~1.5h.

12. The construction method of the cementitious material for improving the performance of the interface zone between new and old concrete in composite slabs according to claim 11, characterized in that, In step 33, the stirring time is 0.5 hours; in step 34, the grinding time is 1 hour.

13. The construction method of the cementitious material for improving the performance of the interface zone between new and old concrete in composite slabs according to claim 7, characterized in that, In step 6, the thickness of the cementitious material coating is 2-3 mm.

Citation Information

Patent Citations

  • A concrete interface agent for wet joints in prefabricated buildings and its preparation method

    CN112341140B

  • Interface agent for enhancing interface bonding performance of new and old concrete and construction method of interface agent

    CN115700230A

  • High-performance concrete gel material for tunnel and application thereof

    CN102838323A